Annihilation - VanderMeer, Jeff (VanderMeer, Jeff. Southern Reach trilogy., 2014)
Area X has claimed the lives of members of eleven expeditions. The twelfth expedition consisting of four women hopes to map the terrain and collect specimens; to record all their observations, scientific and otherwise, of their surroundings and of one another; and, above all, to avoid being contaminated by Area X itself.